An Exploratory Study of Women’s Use of Public Spaces in Greater Khartoum, Sudan. Case Study of Al-Thawra Hara 72, Omdurman (Journal of Building and Road Research, 2022)
This study explores how women’s use of public spaces in Greater Khartoumis restrained by societal norms and violence imposed upon them.Furthermore, women suffer from various forms of harassment that maketheir journeys to work a horrendous daily experience. The study is based onfieldwork conducted in Al-Thawra Hara 72, in which women’s views weregleaned through a questionnaire, focused group discussions; in addition toobservations and safety audits in the neighborhood. It was found thatwomen’s use of public spaces is very limited and is restricted to passiveactivities conducted in conjunction with their children. They tend to avoidgoing out alone or strolling in public spaces to evade violence andharassment. The paper concludes that public spaces lack facilities that couldmake women’s use of them a gratifying experience. Neighborhood planningand urban design measures are proposed to foster more women’s use ofpublic spaces.